STRUKTUR DAN SEBARAN VEGETASI MANGROVE BERDASARKAN KUALITAS LINGKUNGAN BIOFISIK DI TAMAN HUTAN RAYA NGURAH RAI BALI - Ajie Imamsyah; Dietriech Geoffrey Bengen; Meutia Samira Ismet (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2020)
Mangrove are typical coastal plants whose habitat is influenced by tidal and substrate characteristics. Mangrove ecosystems have a variety of functions that can be utilized both in terms of physical, biological, and economic. Utilization of mangrove ecosystems that do not pay attention to environmental sustainability and conservation aspects cause damage of a whole coastal ecosystems. This study aims at analyze the structure and distribution of mangrove vegetation based on biophysical environment quality. This research was conducted on February until March 2017 at Ngurah Rai Forest Park Bali. The results of study show that the conditions of temperature, pH, and salinity are still in accordance with the specified quality standards, however dissolved oxygen has been classified as polluted by anthropogenic waste. The analysis of the sturcture and distribution of mangrove vegetation found that species of S. alba dominated at the location research, followed by oleh R. apiculata, R. mucronata, B. gymnorrhiza, R. stylosa, X. granatum, A. marina, and A. corniculatum. Overall, the results showed that the mangrove condition was in the damaged cateogry with a mangrove density value < 1000 ind/ha. Keywords: Coastal, Environmental, Mangrove, Vegetation